Phosphoric acid doped quaternized poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane and preparation method thereof

A quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane with a microphase separation structure addresses mechanical property degradation in HT-PEMs by enhancing acid absorption and retention, ensuring high proton conductivity and stability.

CN119241786APending Publication Date: 2025-01-03CHANGZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411358538.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

High-temperature proton exchange membranes (HT-PEMs) face challenges in maintaining mechanical properties while achieving high proton conductivity due to phosphoric acid (PA) absorption, which leads to plasticization and stability issues.

Method used

A quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane is developed with a microphase separation structure and quaternization treatment, incorporating long alkyl chains for enhanced acid absorption and retention, and a hydrophobic main chain for improved mechanical properties.

Benefits of technology

The membrane achieves high proton conductivity and maintains mechanical integrity under high temperatures, with improved acid absorption and retention rates, and demonstrates stability in harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241786A_ABST
    Figure CN119241786A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a phosphoric acid doped quaternized poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane and a preparation method thereof. The preparation method comprises the following steps: in a nitrogen environment, adding 2-brominated biphenyl into tetrahydrofuran, uniformly stirring, adding n-butyllithium at-78 DEG C, stirring, adding halogenated alkane, and continuously stirring to obtain 2-alkane biphenyl; the preparation method comprises the following steps: carrying out Friedel-Crafts reaction on 2-alkane biphenyl, biphenyl and 4-imidazole formaldehyde, and carrying out strong acid catalytic polymerization to obtain a poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer; carrying out quaternization treatment to obtain a polymer subjected to quaternization treatment; and finally carrying out phosphoric acid doping to obtain the polymer electrolyte membrane. A long alkyl chain is grafted to a main chain to construct microphase separation, more channels are provided for proton transmission, quaternization treatment is adopted, so that the polymer electrolyte membrane has higher acid absorption capacity, and the ether-free main chain can improve the mechanical property of the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a polymer electrolyte membrane for a high-temperature phosphoric acid fuel cell, and specifically to a phosphoric acid-doped quaternized poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane and a preparation method thereof. Background Art

[0002] On the one hand, proton exchange membrane fuel cells (PEMFCs) use clean energy such as hydrogen and methanol as fuel, reducing the use of traditional fossil fuels and reducing pollution and damage to the environment; on the other hand, they are not restricted by the Carnot cycle and can directly convert chemical energy into electrical energy. They have extremely high working efficiency and have therefore become a hot topic of research in recent decades. PEMFCs can be divided into low-temperature proton exchange membrane fuel cells (LT-PEMFCs) (<100°C) and high-temperature proton exchange membrane fuel cells (HT-PEMFCs) (100-200°C) according to their operating temperature.

[0003] Compared with LT-PEMFCs, HT-PEMFCs have higher reaction electrode kinetics, and use phosphoric acid (PA) as a conductive medium, which is more stable in high temperature environments. Higher operating temperatures simplify water / heat management, making the operation process simpler. However, as the PA doping level increases, the plasticization of PA will cause the mechanical properties of the membrane to decrease, and the stability will deteriorate in high temperature environments. At the same time, the increase in PA absorption will lead to an increase in free acid, which will cause greater damage to the membrane electrode during battery operation.

[0004] At present, the acid absorption rate and acid retention rate of high temperature proton exchange membranes (HT-PEMs) are mainly improved by introducing acid-philic groups such as imidazole, piperidine or other basic groups, quaternizing polymers, designing and synthesizing microporous polymers to utilize the siphon phenomenon, etc. These strategies have reduced PA loss to a certain extent and improved the durability of the battery, but the mechanical properties of the membrane after acid absorption still need to be improved. Therefore, it is urgent to develop a polymer electrolyte membrane with high proton conductivity while maintaining the original mechanical properties. Summary of the invention

[0005] The purpose of the present invention is to provide a quaternized poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane for high temperature phosphoric acid fuel cells in order to overcome the deficiencies of the prior art. Biphenyl has excellent mechanical properties, good thermal stability and chemical stability. After quaternization treatment, it is beneficial for the biphenyl membrane to absorb and retain phosphoric acid, and at the same time, a hydrophobic long alkyl chain is introduced to construct a microphase separation structure, so that high conductivity is obtained while maintaining the original mechanical properties.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a quaternized poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane, whose general structural formula comprises a repeating unit as shown in formula (1),

[0007]

[0008] Wherein, n is an integer of 1-12, x is the molar content of 2-alkanebiphenyl, ranging from 0 to 1;

[0009] The preparation process of the high temperature phosphoric acid membrane is as follows:

[0010] (1) Synthesis of 2-Alkanebiphenyl

[0011] Under nitrogen environment, 2-bromobiphenyl is added to anhydrous tetrahydrofuran and stirred evenly. Under -78°C low temperature environment, n-butyl lithium (the molar amount of n-butyl lithium is 1.3 times that of 2-bromobiphenyl) is slowly added, stirred for 1 hour, and then placed at room temperature and stirred for 3 hours. Then, under -78°C low temperature environment, halogenated alkane (alkane substituted with a halogen atom at one end, such as 2-bromoethane, 3-bromopropane, 4-bromobutane, 5-bromopentane, 8-bromooctane or 12-bromododecane, etc.) is added to the solution (the molar ratio of halogenated alkane to 2-bromobiphenyl is greater than 2:1), and stirred for 1 hour, and then placed at room temperature and stirred for 24 hours. The mixed solution is extracted with ethyl acetate and deionized water, and the organic layer is taken. After removing the ethyl acetate by rotary evaporation, it is placed in an 80°C oven and dried for 24 hours to remove the unreacted halogenated alkane. The remaining solution was purified by silica gel column chromatography using petroleum ether as eluent, and the resulting transparent liquid was the final product.

[0012] (2) Preparation of poly(alkane biphenyl-imidazole formaldehyde-biphenyl)

[0013] The long-chain 2-alkane biphenyl prepared in step (1) is polymerized with biphenyl and 4-imidazole formaldehyde by Friedel-Crafts reaction with strong acid catalysis. 2-alkane biphenyl, 4-imidazole formaldehyde and biphenyl are mechanically stirred and dissolved in dry dichloromethane (the molar amount of 4-imidazole formaldehyde is 1.1 times the total molar amount of 2-alkane biphenyl and biphenyl; the mass fraction of the reactants in the reaction system is 30-50wt%). After being mixed evenly, a mixed solution of methane sulfonic acid (MSA) and trifluoromethane sulfonic acid (TFSA) is slowly added in an ice-water bath (the volume ratio of the two is 4:3). Stirring is continued for 24 hours. After the solution becomes viscous, the reaction is stopped and poured into deionized water for precipitation, washed with deionized water for multiple times until the pH is neutral, and placed in a 60°C oven for drying to obtain a poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer.

[0014] (3) Quaternization treatment

[0015] At 40°C, the polymer was stirred and dissolved in dimethyl sulfoxide (DMSO), potassium carbonate (the molar ratio of polymer to potassium carbonate was 1:2) was added, and after stirring evenly, excess methyl iodide (the molar ratio of polymer to methyl iodide was 1:10) was added. After reacting for 24 hours, the reaction solution was cooled to room temperature, dripped into ethyl acetate for precipitation, and after repeated washing, it was placed in a 60°C oven for drying to obtain the quaternized polymer.

[0016] (4) Preparation of phosphoric acid-doped polymer electrolyte membrane

[0017] The quaternary ammonium polymer was dissolved in DMSO, stirred into a homogeneous solution, and then cast into a film on a clean glass plate, and dried in an oven to prepare a uniform and transparent electrolyte membrane. Finally, the electrolyte membrane was immersed in phosphoric acid (85%) to obtain the target phosphoric acid-doped polymer electrolyte membrane.

[0018] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0019] The present invention constructs microphase separation by grafting long alkyl chains onto the main chain, providing more channels for proton transmission, and adopts quaternization treatment to make the polymer electrolyte membrane have higher acid absorption capacity. The ether-free main chain can improve the mechanical properties of the membrane, and the preparation method is safe and simple with low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is the structural formula and NMR spectrum of 2-butanebiphenyl monomer.

[0021] Figure 2 The structural formula and NMR spectrum of the quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) in Example 1 are shown. DETAILED DESCRIPTION

[0022] The present invention will be further described below with reference to the embodiments.

[0023] Example 1

[0024] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment comprises the following specific steps:

[0025] (1) Preparation of 2-butanebiphenyl monomer: Under nitrogen environment, 1.4g (6mmol) of 2-bromobiphenyl was dissolved in 5ml of anhydrous tetrahydrofuran and stirred to form a homogeneous solution. 3.12ml (7.8mmol) of n-butyl lithium was slowly added under low temperature environment of -78°C, and stirring was continued for 1 hour, and stirring was continued for 3 hours at room temperature. Then, 2.14g (15.6mmol) of n-butyl bromide was added to the solution under low temperature environment of -78°C, and stirring was continued for 1 hour, and then stirred at room temperature for 24 hours. The mixed solution was extracted with ethyl acetate and deionized water, and the organic layer was taken. After removing the ethyl acetate by rotary evaporation, it was placed in an 80°C oven and dried for 24 hours to remove the unreacted n-butyl bromide. The remaining solution was purified by silica gel column chromatography, and petroleum ether was used as the eluent to obtain a transparent liquid as the final product. Its molecular formula is:

[0026]

[0027] (2) Preparation of poly(alkane biphenyl-imidazole formaldehyde-biphenyl)

[0028] The polymerization was carried out by strong acid catalysis of Friedel-Crafts reaction. 2.1g 2-butane biphenyl monomer, 1.54g biphenyl (the molar ratio of the two is 1:1) and 2.11g 4-imidazole formaldehyde, 20mL dichloromethane as solvent were added to a three-necked flask, mechanically stirred for 30 minutes, and after being mixed evenly, 16mL methane sulfonic acid (MSA) and 12mL trifluoromethane sulfonic acid (TFSA) were slowly dripped into the three-necked flask under an ice water bath, and stirring was continued for 24 hours. After the solution became viscous, the reaction was stopped and poured into deionized water for precipitation, washed with deionized water several times until the pH was neutral, and dried in a 60°C oven to obtain a poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer. Its molecular formula is:

[0029]

[0030] (3) Quaternization treatment

[0031] At 40°C, 2g of poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer was uniformly dissolved in DMSO, 2.1g of potassium carbonate (the molar ratio of polymer to potassium carbonate was 1:2) was added, and after stirring evenly, 10.82g of methyl iodide was added at a molar ratio of polymer to methyl iodide of 1:10. After reacting for 24 hours, the reaction solution was cooled to room temperature, dripped into ethyl acetate for precipitation, washed 3 times to remove unreacted methyl iodide and potassium carbonate, and placed in a 60°C oven for drying to obtain a quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer. Its structural formula is:

[0032]

[0033] (4) Take 0.5g of poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer and dissolve it in 10mL DMSO, stir it into a uniform transparent solution, then drop it on a clean glass plate, and put it in a 60℃ oven to dry for 24 hours. Prepare a polymer electrolyte membrane. Immerse the prepared electrolyte membrane in a phosphoric acid solution (85%) at 40℃ for 24 hours so that the phosphoric acid is fully absorbed into the membrane, and remove the residual phosphoric acid on the surface of the polymer electrolyte membrane with dust-free paper.

[0034] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 108.71%, swelling degree was 102.25%; phosphoric acid retention rate was 89.33% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 43.27MPa; proton conductivity at 80°C could reach 56.16mS cm -1 , the proton conductivity at 160°C is 110.39 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppmFe 2+ , 3% H2O2), and placed at 80°C for 120 hours. The remaining weight was measured again and was 96.59%, proving that it has good stability.

[0035] Example 2

[0036] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Embodiment 1, except that: n-octane bromide is used in step (1).

[0037] The quaternized polymer structural formula is:

[0038]

[0039] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 112.91%, swelling degree was 115.83%; phosphoric acid retention rate was 86.23% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 40.28MPa; proton conductivity at 80°C could reach 68.27mS cm -1 , the proton conductivity at 160°C is 121.34 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 95.28%, proving that it has good stability.

[0040] Example 3

[0041] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Embodiment 1, except that dodecane bromide is used in step (1).

[0042] The quaternized polymer structural formula is:

[0043]

[0044] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 120.21%, swelling degree was 125.73%; phosphoric acid retention rate was 83.21% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 21.59MPa; proton conductivity at 80°C could reach 87.49mS cm -1 , the proton conductivity at 160°C is 133.63 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 93.51%, proving that it has good stability.

[0045] Example 4

[0046] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the ratio of 2-alkanebiphenyl to biphenyl is 3:7.

[0047] The quaternized polymer structural formula is:

[0048]

[0049] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 101.35%, swelling degree was 98.87%; phosphoric acid retention rate was 91.21% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 66.48MPa; proton conductivity at 80°C could reach 48.96mS cm -1 , the proton conductivity at 160℃ is 107.27mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 98.87%, proving that it has good stability.

[0050] Example 5

[0051] This embodiment provides a method for preparing a polymer electrolyte membrane with a microphase separation structure, which is basically the same as that in Embodiment 1, except that in step (2), the ratio of 2-alkanebiphenyl to biphenyl is 7:3.

[0052] The quaternized polymer structural formula is:

[0053]

[0054] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 115.54%, swelling degree was 109.91%; phosphoric acid retention rate was 87.69% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 35.39MPa; proton conductivity at 80°C could reach 65.43mS cm -1 , the proton conductivity at 160°C is 119.87 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 94.31%, proving that it has good stability.

[0055] Example 6

[0056] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Example 1, except that: n-octane bromide is used in step (1), and the ratio of 2-alkanebiphenyl to biphenyl in step (2) is 3:7.

[0057] The quaternized polymer structural formula is:

[0058]

[0059] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 105.87%, swelling degree was 109.25%; phosphoric acid retention rate was 88.89% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 51.37MPa; proton conductivity at 80°C could reach 59.77mS cm -1 , the proton conductivity at 160℃ is 113.58mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 96.99%, proving that it has good stability.

[0060] Example 7

[0061] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Example 1, except that: octane bromide is used in step (1), and the ratio of 2-alkanebiphenyl to biphenyl in step (2) is 7:3.

[0062] The quaternized polymer structural formula is:

[0063]

[0064] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 125.32%, swelling degree was 121.48%; phosphoric acid retention rate was 85.02% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 31.21MPa; proton conductivity at 80°C could reach 81.95mS cm -1 , the proton conductivity at 160°C is 129.87 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 93.87%, proving that it has good stability.

[0065] Example 8

[0066] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Example 1, except that dodecane bromide is used in step (1), and the ratio of 2-alkanebiphenyl to biphenyl in step (2) is 3:7.

[0067] The quaternized polymer structural formula is:

[0068]

[0069] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 113.28%, swelling degree was 110.23%; phosphoric acid retention rate was 85.97% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 39.47MPa; proton conductivity at 80°C could reach 70.31mS cm -1 , the proton conductivity at 160°C is 124.97 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 96.03%, proving that it has good stability.

[0070] Example 9

[0071] The method for preparing a polymer electrolyte membrane with a microphase separation structure provided in this embodiment is basically the same as that in Example 1, except that dodecane bromide is used in step (1), and the ratio of 2-alkanebiphenyl to biphenyl in step (2) is 7:3.

[0072] The quaternized polymer structural formula is:

[0073]

[0074] The performance parameters of the polymer electrolyte membrane were measured as follows: phosphoric acid absorption rate was 127.34%, swelling degree was 132.58%; phosphoric acid retention rate was 80.77% after being placed at 100°C for 120 hours; tensile strength after acid soaking was 13.01MPa; proton conductivity at 80°C could reach 90.27mS cm -1 , the proton conductivity at 160°C is 147.39 mS cm -1 ; The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H2O2), placed at 80°C for 120 hours, and its remaining weight was measured again to be 91.59%, proving that it has good stability.

[0075] Comparative Example 1

[0076] The preparation method of the polymer electrolyte membrane without alkane side chains provided in this embodiment is basically the same as that in embodiment 1, except that: 2-butanebiphenyl does not need to be prepared in step (1), and only biphenyl (the molar amount of 4-imidazolecarboxaldehyde is 1.1 times the molar amount of biphenyl; the mass fraction of the reactant (biphenyl) in the reaction system is 40wt%) is used in step (2). Biphenyl and 4-imidazolecarboxaldehyde are polymerized to prepare a polymer electrolyte membrane with biphenyl as the main chain, and its structural formula is:

[0077]

[0078] Under the same experimental conditions, the performance parameters of the polymer electrolyte membrane were measured as follows: the proton conductivity at 80°C was 34.21 mS cm -1 , can reach 98.87mS cm at 160℃ -1 , the conductivity is low; the tensile strength after acid soaking is 73.34Mpa, the strength is relatively high; the acid absorption rate at 40℃ is 95.39%, and the swelling degree is 92.31%.

[0079] Comparative Example 2

[0080] This embodiment provides a method for preparing a polymer electrolyte membrane based on 2-butanebiphenyl polymer, which is basically the same as that of embodiment 1, except that in step (2), only 2-butanebiphenyl is used instead of biphenyl (the molar amount of 4-imidazolecarboxaldehyde is 1.1 times the molar amount of 2-butanebiphenyl; the mass fraction of the reactant (2-butanebiphenyl) in the reaction system is 40wt%). The polymer electrolyte membrane prepared by polymerization of 2-butanebiphenyl and 4-imidazolecarboxaldehyde has the structural formula:

[0081]

[0082] Under the same experimental conditions, the performance parameters of the polymer electrolyte membrane were measured as follows: the proton conductivity at 80°C was 70.25 mS cm -1 , it can reach 129.81mS cm at 160℃ -1 , the electrical conductivity is relatively high; the tensile strength after acid soaking is 4.64Mpa; the acid absorption rate at 40°C is 136.21%, and the swelling degree is 149.87%.

[0083] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane, characterized in that: The general chemical structure of the polymer electrolyte membrane is a repeating unit as shown in formula (1), In the formula, n is an integer of 1-12, and x is the molar content of 2-alkanebiphenyl, ranging from 0-1.

2. A method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane as claimed in claim 1, characterized in that: The preparation method steps are as follows: (1) Synthesis of 2-Alkanebiphenyl Under a nitrogen environment, 2-bromobiphenyl is added to anhydrous tetrahydrofuran, and stirred evenly. n-Butyl lithium is added at -78°C, and stirred for 1 hour, and then stirred at room temperature for 3 hours. Then, a halogenated alkane is added to the solution at -78°C, and stirred for 1 hour, and then stirred at room temperature for 24 hours. The mixed solution is extracted with ethyl acetate and deionized water, and the organic layer is taken, and the ethyl acetate is removed by rotary evaporation, and then dried in an oven at 80°C for 24 hours to remove unreacted halogenated alkane. The remaining solution is purified by silica gel column chromatography, and petroleum ether is used as an eluent to obtain a transparent liquid 2-alkanebiphenyl. (2) Preparation of poly(alkane biphenyl-imidazole formaldehyde-biphenyl) Dissolve 2-alkane biphenyl, 4-imidazole formaldehyde and biphenyl in dry dichloromethane by mechanical stirring, and after being evenly mixed, add a mixed solution of methane sulfonic acid and trifluoromethane sulfonic acid in an ice water bath, and continue stirring for 24 hours; after the solution becomes viscous, stop the reaction and pour into deionized water for precipitation, wash with deionized water until the pH is neutral, and put into a 60° C. oven for drying to obtain a poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer; (3) Quaternization treatment At 40° C., the polymer prepared in step (2) was dissolved in dimethyl sulfoxide by stirring, potassium carbonate was added, and iodomethane was added after stirring. After reacting for 24 hours, the reaction solution was cooled to room temperature, and ethyl acetate was added dropwise for precipitation. After repeated washing, the solution was placed in a 60° C. oven for drying to obtain a quaternized polymer. (4) Preparation of phosphoric acid-doped polymer electrolyte membrane The quaternary ammonium polymer was dissolved in DMSO, stirred into a homogeneous solution, and then cast into a film on a clean glass plate, which was dried in an oven to prepare a uniform and transparent electrolyte membrane. Finally, the electrolyte membrane was immersed in 85% phosphoric acid to obtain a phosphoric acid-doped polymer electrolyte membrane.

3. The method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane according to claim 2, characterized in that: In the step (1), the molar amount of n-butyl lithium is 1.3 times that of 2-bromobiphenyl.

4. The method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane according to claim 2, characterized in that: In the step (1), the molar ratio of the halogenated alkane to 2-bromobiphenyl is greater than 2:1, and the halogenated alkane is: 2-bromoethane, 3-bromopropane, 4-bromobutane, 5-bromopentane, 8-bromooctane or 12-bromododecane.

5. The method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane according to claim 2, characterized in that: In the step (2), the molar amount of 4-imidazole carboxaldehyde is 1.1 times the total molar amount of 2-alkane biphenyl and biphenyl, and the mass fraction of the reactants in the reaction system is 30-50wt%.

6. The method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane according to claim 2, characterized in that: In the step (2), the volume ratio of methanesulfonic acid to trifluoromethanesulfonic acid is 4:

3.

7. The method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane according to claim 2, characterized in that: In the step (3), the molar ratio of the polymer to potassium carbonate is 1:

2.

8. The method for preparing the phosphoric acid-doped quaternized poly(alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane according to claim 2, characterized in that: In the step (3), the molar ratio of the polymer to methyl iodide is 1:

10.

9. An application of the phosphoric acid-doped quaternized poly (alkane biphenyl-imidazole formaldehyde-biphenyl) polymer electrolyte membrane as claimed in claim 1, characterized in that: The polymer electrolyte membrane is used as a proton exchange membrane of a high-temperature proton exchange membrane fuel cell.

Citation Information

Cited By

  • High-temperature proton exchange membrane as well as preparation method and application thereof

    CN120854624A

  • Two-dimensional nano-material-based proton exchange membrane with sandwich structure and preparation method and application of two-dimensional nano-material-based proton exchange membrane

    CN121790452A